Analysis Of The Influence Of Work Environment, Work Discipline And Work Facilities On The Performance Of Asn Employees In The Department Of Industry, Trade, Energy, And Mineral Resources Of North Sumatra Province - Khairunnisa Annabila Pane; Yohny Anwar; Teguh Wahyono (International Journal of Management, Economic and Accounting, 2025)
The results of this study aim to know and analyze the influence of work environment, work discipline, and work facilities on the performance of ASN employees of the North Sumatra Provincial Department of Industry, Trade, Energy and Mineral Resources. This study uses a quantitative approach. The sample in the study was 72 ASN employees with random sampling techniques. The results of this study show that the work environment partially has a positive and significant effect on employee performance with a tcal value of 4.839 > ttable 1.995 and a significant value of 0.00 < 0.05. Work Discipline partially has a positive and significant effect on employee performance with a tcal value of 5,998 > ttable 1.995 and significant values 0.00 < 0.05. Work Facilities did not have a positive and significant effect on employee performance with a tcount value of 0.045 < ttable 1.995 and a significant value of 0.964 > 0.05. Work Environment, Work Discipline, and Work Facilities simultaneously have an influence on the Performance of ASN Employees of the Department of Industry, Trade, Energy and Mineral Resources of North Sumatra Province with a value of Fcal 103,893 > Ftable 2.73 and a significant value of 0.00 < 0.05.